Analisis Faktor-Faktor Yang Mempengaruhi Premature Sign-Off Of Audit Procedure Pada KAP di Jawa Tengah - Nanik Sri Utaminingsih; Hayuning Tyas (Conference In Business, Accounting, And Management (CBAM), 2012)
The study aims at testing the effect of job level, professional ethics and locus of control on the premature sign off. The population used in this study is all auditor working at the Public Accountant Office in Central Java. The population of the study includes junior auditors, senior auditors, managers and partners. By using convenience technique sampling, the study collected 75 auditors as samples.Primary data are collected using five-scale likert questioners. Moreover, the study employs partial least square (PLS) to analys the data. The study conclude that internal locus of control does not impact on the premature sign-off. The job level affect on the premature sign off. At the same time, job level also has positive impact on professional ethics. On the other hand, professional ethics, negatively affect premature sign off. The results show that the direct effect of job level on premature sign off is greather than the indirect effect of job level on premature sign off by using professional ethics as a moderating variable.Keywords: job level, professional ethics, locus of control, premature sign off.